How Relevance Affects Understanding of Conflicts Between Multiple Documents: An Eye‐Tracking Study. Issue 4 (25th October 2019) - Stadtler, Marc; Scharrer, Lisa; Bromme, Rainer
Abstract: The authors examined how information relevance affects readers' understanding of conflicting information in multiple documents and how relevance affects the processing of conflicting information on a moment‐by‐moment level. Sixty‐four undergraduate students read a set of documents about a medical topic containing three intertextual conflicts addressing subtopics that were either highly relevant or irrelevant to the readers' task. Eye movements were recorded during reading, and afterward, readers' memory for conflicting information and their ability to apply their knowledge about the conflicting information was assessed. Relevance had a powerful influence on readers' understanding of conflicts between multiple documents: Readers for whom the intertextual conflicts were relevant remembered conflicting information better and reported conflicts more frequently than readers for whom the conflicts were irrelevant. The time course of this effect revealed that relevance exerts its influence only during a later stage of processing. Readers appear to initially detect conflicts regardless of their relevance, but only readers for whom conflicts are relevant invest the additional regulatory effort needed to include them in their mental representation.